Economic Values and CO2 Simulation on the Application of LPG for Public Fleets in Magelang, Indonesia: Executive Data to Support the Clean City Program - Setiyo, Muji; Widodo, Eko Muh; Rosyidi, Muhammad Imron; Purnomo, Tuessi Ari; Rahardja, Bayu Sindhu; Suryantoro, Suryantoro (Periodica Polytechnica Transportation Engineering, 2020)
The implementation of the ASEAN Clean Tourist City Standard caused restlessness among public fleet operators and the Department of Transportation of Magelang City. Therefore, this article presents the prediction of economic value and environmental benefits of public fleet in Magelang that will be converted from gasoline to LPG. Investment feasibility parameters, such as Break Event Point (BEP), Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP) are presented through three financing scenarios compared with the current gasoline price at the fuel station, RON 88 and RON 90. Simulation results indicate that investment is feasible with the government providing fiscal incentives through the procurement of converter kits. The wages of the public fleet crew under Minimum Wage City will rise by 30 % and 70 % to switch from gasoline RON 88 and gasoline RON 90, respectively. Meanwhile, environmental benefits are also expected to improve, with CO2 emission reduction of 320.46 tons/year or about 11 % of gasoline usage. These two benefits (economics and environmental) are expected to support the clean city program in Magelang City, Indonesia.